Comparison Study on Cancel Culture as an Impact and Public Figure Scandal in Indonesia and Overseas - Miranda Putri, Vania; Octavia, Ivana; Tri Nuryanto, Hery; Nurhajati, Lestari (Communicare : Journal of Communication Studies, 2024)
This research aims to comprehend the phenomenon known as "cancel culture," explicitly examining its operations in Indonesia compared to other nations. The study seeks to identify the mechanisms, social dynamics, and cultural discrepancies that shape the repercussions of cancel culture on prominent individuals and society. Moreover, it delves into the psychological ramifications it engenders, along with proposed measures to mitigate its adverse effects. Employing a qualitative methodology with a case study orientation, this research scrutinizes the cancel culture phenomenon. Techniques for data collection encompass a thorough literature review and observations across diverse social media platforms. Subsequently, the gathered data is scrutinized through a narrative perspective utilizing the cancel culture framework. Furthermore, the research incorporates ethnographic methodologies to investigate online community culture and associated phenomena. Findings from this study illustrate the intricate consequences of canceling culture on public figures and society, showcasing notable distinctions between Indonesia and other global contexts. In Indonesia, this trend can paradoxically elevate the profile of the affected individual, while elsewhere, it commonly results in professional setbacks and enduring repercussions. Noteworthy psychological effects, such as depression and suicidal inclinations stemming from public shame and social ostracism, were uncovered. The illustrated case study demonstrates the diverse outcomes encountered by public figures on both domestic and international platforms. To alleviate the adverse impacts of cancel culture, the study proposes strategies like emotional backing, constructive discourse, answerability, and professional intervention.